A critical appraisal of the quality of head and neck cancer imaging guidelines using the AGREE II tool: A EuroAIM initiative. (21st December 2018) - Romeo, Valeria; Stanzione, Arnaldo; Cocozza, Sirio; Ugga, Lorenzo; Cuocolo, Renato; Brunetti, Arturo; Bisdas, Sotirios
Abstract: Background: Diagnostic imaging guidelines are increasingly embraced in oncologic imaging in order to improve examinations appropriateness and technical quality. The usefulness of guidelines employment in clinical practice is dramatically related to the quality of the guidelines themselves. However, an extreme variability in guidelines' quality may occur. Following a European Network for the Assessment of Imaging in Medicine (EuroAIM) initiative, the aim of this study was to assess the quality of the available guidelines regarding head and neck cancer (HNC) imaging. Methods: A literature search was conducted to identify imaging guidelines focused on HNC. Selected guidelines were evaluated by four independent appraisers using the Appraisal of Guidelines for Research & Evaluation version 2.0 (AGREE II) tool, which comprises 23 key items, rated on a 7‐point scale (1—strongly disagree to 7—strongly agree) and organized within six domains. For each domain, the intraclass correlation coefficient (ICC) was used to assess the agreement among appraisers' scores. Results: After literature search, three guidelines were selected and evaluated. One guideline scored "average" as overall quality, while the remaining two scored a "low" overall quality. The highest result (total score = 75.0% ± 19.3%) was obtained in domain 4 (Clarity of presentation) while the lowest (total score = 27.1% ± 4.2%) in domain 6 (Editorial independence). ICC analysis showed a very good agreement (range: 0.932‐0.961) among the four appraisers. Conclusions: Our results showed a heterogeneous quality of existing guidelines in HNC imaging. Issues raised from this appraisal should be considered when developing future guidelines on HNC imaging. Abstract : The quality of existing guidelines in head and neck cancer imaging is heterogeneous according to the AGREE II tool. Issues raised from this appraisal should be considered by developers of future guidelines in head and neck cancer imaging.